The Influence of Accessibility, Design, and BUMDes Website Features on the Effectiveness of BUMDes Management in Sumberpucung District - Sanputra, Adrian Hartanto Darma; Sidharta, Eka Ananta; Pratiwi, Venni Ayunda; Ahyar, Shynta Nuril Rahmawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
Good management of Village-Owned Enterprises (BUMDes) is very important to support economic growth in the region. The BUMDes website of Sumberpucung District has been developed to support the effectiveness of BUMDes management there. This study aims to explore the influence of the existence of the website in terms of accessibility, interface design, and website features on the effectiveness of BUMDes management. Research data were obtained through literature studies and filling out questionnaires from 25 research samples. The research instruments used were tested through validity and reliability tests, and the data and regression models used were tested through classical assumption tests and hypothesis tests. The results of the study showed that accessibility, interface design, and website features had a significant positive effect on the effectiveness of BUMDes management in Sumberpucung District. The three variables also had a simultaneous effect on the effectiveness of BUMDes management. The results of this study are expected to be a consideration in the management of BUMDes in Sumberpucung District in the future and provide broader insights regarding the use of information technology and organizational management.